Electro-tactile modulation of muscle activation and intermuscular coordination in the human upper extremity - Hy Doan; Shahabedin Tavasoli; Gang Seo; Hyung-Soon Park; Hangue Park; Jinsook Roh (Scientific Reports)
Abstract Electro-tactile stimulation (ETS) can be a promising aid in augmenting sensation for those with sensory deficits. Although applications of ETS have been explored, the impact of ETS on the underlying strategies of neuromuscular coordination remains largely unexplored. We investigated how ETS, alone or in the presence of mechano-tactile environment change, modulated the electromyogram (EMG) of individual muscles during force control and how the stimulation modulated the attributes of intermuscular coordination, assessed by muscle synergy analysis, in human upper extremities. ETS was applied to either the thumb or middle fingertip which had greater contact with the handle, grasped by the participant, and supported a target force match. EMGs were recorded from 11 arm muscles of 15 healthy participants during three-dimensional exploratory force control. EMGs were modeled as the linear combination of muscle co-activation patterns (the composition of muscle synergies) and their activation profiles. Individual arm muscle activation changed depending on the ETS location on the finger. The composition of muscle synergies was conserved, but synergy activation coefficients altered reflecting the effects of electro-tactile modulation. The mechano-tactile modulation tended to decrease the effects of ETS on the individual muscle activation and synergy activation magnitude. This study provides insights into sensory augmentation and its impact on intermuscular coordination in the human upper extremity.